2008
DOI: 10.1136/oem.2007.035147
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain in drivers exposed to whole body vibration: analysis of a dose–response pattern

Abstract: The investigation found a dose-response pattern between WBV exposure and driving-related LBP. No indication of a dose-response pattern was found between WBV exposure and 12-month LBP. Although this dose-response pattern is only an indication, these findings imply that WBV exposure might contribute to the onset of driving-related LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 29 publications
(34 reference statements)
9
48
2
4
Order By: Relevance
“…An estimation of physical demands by self-reports has been criticised as being inaccurate, especially for the more complex load-bearing activities carried out by employees [67]. Otherwise, it has been shown that workload and occupational physical activity can be reliably assessed by questionnaires and that questionnaires can classify groups with heterogeneous occupational tasks [68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimation of physical demands by self-reports has been criticised as being inaccurate, especially for the more complex load-bearing activities carried out by employees [67]. Otherwise, it has been shown that workload and occupational physical activity can be reliably assessed by questionnaires and that questionnaires can classify groups with heterogeneous occupational tasks [68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…Although the load of whole body vibrations is considered to be associated with LBP [71][72][73], we excluded this variable because we considered this exertion as an external mechanical force and not as a result of physical activity behaviour, which was the focus of our research. It is generally agreed that the aetiology of back pain is multifactorial [74] and that physical load only partially explains the prevalence of back pain [75].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational drivers suffer from many musculoskeletal health problems, such as lower back pain, sciatica, lumbar vertebral early degeneration, and herniated intervertebral discs. The main etiology is thought to be vibration hazard, especially wholebody vibration 23,24) . Many researchers have found that specific vibration frequencies can cause a resonance effect with the body's vertebral system 25−27) , and this resonance energy may cause damage to the vertebral system 28) .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that prevalence of back pain in full-time workers is 25.3% compared with 19.1% in part-time workers, and the prevalence of back pain is more than 23% among workers who worked over 36 hours weekly and more than 38% among workers who worked over 45 hours weekly (Eurofound, 2007). In a study of LBP among drivers, an uncomfortable working station (Alperovitch-Najenson, 2010), long career (Szeto & Lam, 2007), high daily vibration exposure (Bovenzi, 2010), annual driving mileage (Porter & Gyi, 2002) and long daily driving time, and cumulative total hours of exposure (Tiemessen et al, 2008) tended to increase the prevalence of back troubles. Moreover, the prevalence of LBP is significantly higher in those currently or previously exposed to manual material handling and/or tiring postures (20%) compared with those never exposed to these strains (11%) in men below the retirement aged 45-59 (Plouvier et al, 2011).…”
Section: Onset Of Accidental Lbpmentioning
confidence: 99%